2007
DOI: 10.1038/sj.bjp.0707435
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of proteinase‐activated receptor 1 and increased contractile responses to thrombin after subarachnoid haemorrhage

Abstract: Background and purpose: The mechanism for the development of post-haemorrhagic cerebral vasospasm after subarachnoid haemorrhage (SAH) still remains unknown. Experimental approach: We investigated the role of thrombin and its receptor PAR 1 in the development of hyper-contractility of the basilar artery in a rabbit double haemorrhage model, which received two injections of autologous blood into the cisterna magna. Key results: In the basilar artery isolated from the control rabbits, thrombin, only at 10 units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 35 publications
5
38
0
Order By: Relevance
“…This study showed the upregulation of receptors for all these agonists in SAH. The upregulation of ET A receptor and PAR 1 is consistent with the observations of the previous reports (Ide et al, 1989;Itoh et al, 1994;Maeda et al, 2007;Vatter et al, 2007), whereas no study has previously reported the upregulation of a 1 -adrenoceptor in SAH. The upregulation of PAR 1 and a 1 -adrenoceptor may be consistent with the enhancement of the maximal response.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study showed the upregulation of receptors for all these agonists in SAH. The upregulation of ET A receptor and PAR 1 is consistent with the observations of the previous reports (Ide et al, 1989;Itoh et al, 1994;Maeda et al, 2007;Vatter et al, 2007), whereas no study has previously reported the upregulation of a 1 -adrenoceptor in SAH. The upregulation of PAR 1 and a 1 -adrenoceptor may be consistent with the enhancement of the maximal response.…”
Section: Discussionsupporting
confidence: 92%
“…The general impairment of the receptor inactivation may be consistent with previous reports showing the enhanced contractile response to various receptor ligands (Hansen-Schwartz et al, 2003;Itoh et al, 1994;Kai et al, 2007;Kai et al, 2008;Maeda et al, 2009;Maeda et al, 2007;Vatter et al, 2007). However, the impaired receptor inactivation exerts a significant effect especially on the activity of ET A receptor and PAR 1 .…”
Section: Discussionsupporting
confidence: 91%
“…In the basilar artery of the control animals, the contractions induced by thrombin, PAR 1 -AP, endothelin, and phenylephrine gradually decreased after reaching the maximal level of contraction (Fig. 1B) (22,24). However, after SAH, the contractile response to these agonists was not only enhanced as mentioned above, but also prolonged (Fig.…”
Section: Impairment Of the Feedback Regulation Of The Contractile Resmentioning
confidence: 87%
“…In contrast, in the basilar artery isolated from the SAH model animals, thrombin induced a significantly enhanced contraction at lower concentrations (22 -24). The enhanced reactivity was also observed with a agonist peptide for proteinase-activated receptor (PAR) 1 (PAR 1 -AP), but not for PAR 4 (PAR 4 -AP), thus suggesting that PAR 1 is a major receptor mediating the contractile effect of thrombin after SAH (22,23). Similar enhancement of the reactivity was also observed with platelet-derived growth factor, an α-adrenoceptor agonist, and endothelin-1, but not for high K + -depolarization or phorbol ester (24,25).…”
Section: Up-regulation Of the Thrombin Receptor During Subarachnoid Hmentioning
confidence: 89%
“…Previously, we demonstrated that thrombin differentiates normal lung fibroblasts to a myofibroblast phenotype via the PAR-1 receptor and via a PKC-dependent pathway [6]. Thrombin is known to induce ET-1 in various cell types [12,13]. Moreover, ET-1 and thrombin have similar pro-fibrogenic effects in lung fibroblasts and endothelial cells [14][15][16].…”
Section: Introductionmentioning
confidence: 99%